Design Of An Easy To Clean Ceiling Fan For Domestic Users - Musa, Zainal (Universiti Sains Malaysia, 2017)
This thesis is based on the project about design and fabrication of an easy cleaning ceiling fan for domestic user. This project helps domestic consumers to enable them to perform cleaning ceiling fans. The fabrication of this product started with surveying in market about the product, specification analysis, concept designing and fabrication of the product. The selected product from the market were analysis and investigation. One types of the product that suitable and fit all the specification was chosen to fabricate. The investigation was made in scope of the constraint that may occur for the development of the product and relevance of the product manufacturing processes. This product have been fabricate according to engineering method through many fabrication process such as cutting, drilling and assembling. The results of this study prove that the new design of the ceiling fan easier and faster to wash. For development of this project and future works, some suggestion was made for upgrading the product. The suggestion are to make sure this product will competitive with the existing products in the marketing.